Evaluating tests in medical diagnosis-Combining machine learning with game-theoretical concepts - Pfannschmidt, Karlson; Hüllermeier, Eyke; Held, S.; Neiger, R. (In Proceedings IPMU 16th International Conference on Information Processing and Management of Uncertainty in Knowledge-Based Systems, Part 1, Eindhoven, The Netherlands)

GUM-konforme Unsicherheitsabschätzung bei inversen Problemen am Beispiel akustischer Transmissionsmessungen - Feldmann, Nadine; Bause, Fabian; Henning, Bernd

Die Corpusanalyse multimodaler Erzählungen am Beispiel graphischer Romane - Dunst, Alexander; Hartel, Rita (DHd-Tagung 2015, Modellierung - Vernetzung - Visualisierung, Die Digital Humanities als fächerübergreifendes Forschungsparadigma)

Short Randomizable Aggregatable Signatures: Constructions and Security Analysis - Dallmeier, Fynn

Requirements Specification-by-Example Using a Multi-Objective Evolutionary Algorithm - van Rooijen, Lorijn; Hamann, Heiko (Proceedings of 24th IEEE International Requirements Engineering Conference (RE 2016))
A task at the beginning of the software development process is the creation of a requirements specification. The requirements specification is usually created by a software engineering expert. We try to substitute this expert by a domain expert (the user) and formulate the problem of creating requirements specifications as a search-based software engineering problem. The domain expert provides only examples of event sequences that describe the behavior of the required software program. These examples are represented by simple sequence diagrams and are divided into two subsets: positive examples of required program behavior and negative examples of prohibited program behavior. The task is then to synthesize a generalized requirements specification that usefully describes the required software. We approach this problem by applying a genetic algorithm and evolve deterministic finite automata (DFAs). These DFAs take the sequence diagrams as input that should be either accepted (positive example) or rejected (negative example). The problem is neither to find the minimal nor the most general automaton. Instead, the user should be provided with several appropriate automata from which the user can select, or which help the user to refine the examples given initially. We present the context of our research ("On-The-Fly Computing"), present our approach, report results indicating its feasibility, and conclude with a discussion.

CavSimBase: A database for large scale comparison of protein binding sites - Leinweber, M.; Fober, T.; Strickert, M.; Baumgärtner, L.; Klebe, G.; Freisleben, B.; Hüllermeier, Eyke (IEEE Transactions on Knowledge and Data Engineering)

Reconfigurable Accelerators in the World of General-Purpose Computing - Kenter, Tobias

Program Slicing: A Way of Separating WHILE Programs into Precise and Approximate Portions - Zhang, Guangli

NetIDE: All-in-one framework for next generation, composed SDN applications - Gutierrez, P. A. Aranda; Rojas, E.; Schwabe, A.; Stritzke, C.; Doriguzzi-Corin, R.; Leckey, A.; Petralia, G.; Marsico, A.; Phemius, K.; Tamurejo, S. (2016 IEEE NetSoft Conference and Workshops (NetSoft))

Proceedings of the 17th ACM International Symposium on Mobile Ad Hoc Networking and Computing (MobiHoc)

A non-disruptive automated approach to update SDN applications at runtime - Marsico, Antonio; Doriguzzi-Corin, Roberto; Gerola, Matteo; Siracusa, Domenico; Schwabe, Arne (NOMS 2016 - 2016 IEEE/IFIP Network Operations and Management Symposium)

Empowering network operating systems with memory management techniques - Doriguzzi-Corin, Roberto; Siracusa, Domenico; Salvador, Elio; Schwabe, Arne (NOMS 2016 - 2016 IEEE/IFIP Network Operations and Management Symposium)

Algorithm Engineering Aspects of Real-Time Rendering Algorithms - Fischer, Matthias; Jähn, Claudius; Meyer auf der Heide, Friedhelm; Petring, Ralf (Algorithm Engineering)
Defining, measuring, and comparing the quality and efficiency of rendering algorithms in computer graphics is a demanding challenge: quality measures are often application specific and efficiency is strongly influenced by properties of the rendered scene and the used hardware. We survey the currently employed evaluation methods for AQ1 the development process of rendering algorithms. Then, we present our PADrend framework, which supports systematic and flexible development, evaluation, adaptation, and comparison of rendering algorithms, and provides a comfortable and easy-to-use platform for developers of rendering algorithms. The system includes a new evaluation method to improve the objectivity of experimental evaluations of rendering algorithms.

The impact of the Gabriel subgraph of the visibility graph on the gathering of mobile autonomous robots - Li, Shouwei; Meyer auf der Heide, Friedhelm; Podlipyan, Pavel (Algorithms for Sensor Systems, Proceedings of the 12th International Symposium on Algorithms and Experiments for Wireless Sensor Networks (ALGOSENSORS))

Asymptotically Optimal Gathering on a Grid - Cord-Landwehr, Andreas; Fischer, Matthias; Jung, Daniel; Meyer auf der Heide, Friedhelm (Proceedings of the 28th ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
In this paper, we solve the local gathering problem of a swarm of n indistinguishable, point-shaped robots on a two dimensional grid in asymptotically optimal time O(n) in the fully synchronous FSYNC time model. Given an arbitrarily distributed (yet connected) swarm of robots, the gathering problem on the grid is to locate all robots within a 2x2- sized area that is not known beforehand. Two robots are connected if they are vertical or horizontal neighbors on the grid. The locality constraint means that no global control, no compass, no global communication and only local vision is available; hence, a robot can only see its grid neighbors up to a constant L1-distance, which also limits its movements. A robot can move to one of its eight neighboring grid cells and if two or more robots move to the same location they are merged to be only one robot. The locality constraint is the significant challenging issue here, since robot move- ments must not harm the (only globally checkable) swarm connectivity. For solving the gathering problem, we provide a synchronous algorithm { executed by every robot { which ensures that robots merge without breaking the swarm con- nectivity. In our model, robots can obtain a special state, which marks such a robot to be performing specific connec- tivity preserving movements in order to allow later merge operations of the swarm. Compared to the grid, for gath- ering in the Euclidean plane for the same robot and time model the best known upper bound is O(n^2).

Gathering a Closed Chain of Robots on a Grid - Abshoff, Sebastian; Cord-Landwehr, Andreas; Fischer, Matthias; Jung, Daniel; Meyer auf der Heide, Friedhelm (Proceedings of the 30th International Parallel and Distributed Processing Symposium (IPDPS))
We consider the following variant of the two dimensional gathering problem for swarms of robots: Given a swarm of n indistinguishable, point shaped robots on a two dimensional grid. Initially, the robots form a closed chain on the grid and must keep this connectivity during the whole process of their gathering. Connectivity means, that neighboring robots of the chain need to be positioned at the same or neighboring points of the grid. In our model, gathering means to keep shortening the chain until the robots are located inside a 2*2 subgrid. Our model is completely local (no global control, no global coordinates, no compass, no global communication or vision, ...). Each robot can only see its next constant number of left and right neighbors on the chain. This fixed constant is called the viewing path length. All its operations and detections are restricted to this constant number of robots. Other robots, even if located at neighboring or the same grid point cannot be detected. Only based on the relative positions of its detectable chain neighbors, a robot can decide to obtain a certain state. Based on this state and their local knowledge, the robots do local modifications to the chain by moving to neighboring grid points without breaking the chain. These modifications are performed without the knowledge whether they lead to a global progress or not. We assume the fully synchronous FSYNC model. For this problem, we present a gathering algorithm which needs linear time. This result generalizes a result, where an open chain with specified distinguishable (and fixed) endpoints is considered.

On Competitive Algorithms for Approximations of Top-k-Position Monitoring of Distributed Streams - Macker, Alexander; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (2016 IEEE International Parallel and Distributed Processing Symposium (IPDPS))

Cost-efficient Scheduling on Machines from the Cloud - Mäcker, Alexander; Malatyali, Manuel; Meyer auf der Heide, Friedhelm; Riechers, Sören (arXiv:1609.01184)
We consider a scheduling problem where machines need to be rented from the cloud in order to process jobs. There are two types of machines available which can be rented for machine-type dependent prices and for arbitrary durations. However, a machine-type dependent setup time is required before a machine is available for processing. Jobs arrive online over time, have machine-type dependent sizes and have individual deadlines. The objective is to rent machines and schedule jobs so as to meet all deadlines while minimizing the rental cost. Since we observe the slack of jobs to have a fundamental influence on the competitiveness, we study the model when instances are parameterized by their (minimum) slack. An instance is called to have a slack of $β$ if, for all jobs, the difference between the job's release time and the latest point in time at which it needs to be started is at least $β$. While for $β < s$ no finite competitiveness is possible, our main result is an $O(\frac{c}{ε} + \frac{1}{ε^3})$-competitive online algorithm for $β = (1+ε)s$ with $\frac{1}{s} ≤ ε ≤ 1$, where $s$ and $c$ denotes the largest setup time and the cost ratio of the machine-types, respectively. It is complemented by a lower bound of $Ω(\frac{c}{ε})$.

Predicting Rankings of Software Verification Tools Using Kernels for Structured Data - Czech, Mike

Ein ultraschallbasiertes inverses Messverfahren zur Charakterisierung viskoelastischer Materialparameter von Polymeren - Bause, Fabian

Anwendungsm\"oglichkeiten der Schallfeldvisualisierung in der Ultraschallmesstechnik - Olfert, Sergei; Henning, Bernd

5.3.1 - Ein ultraschallbasiertes inverses Messverfahren zur Charakterisierung viskoelastischer Materialparameter von Polymeren - Bause, F.; Henning, Bernd

3.2.3 - Direktgravimetrischer Partikelmasse-Sensor zur quasikontinuierlichen Emissionsmessung - Ester, S.; Struschka, M.; Henning, Bernd

Towards the price of leasing online - Abshoff, Sebastian; Kling, Peter; Markarian, Christine; Meyer auf der Heide, Friedhelm; Pietrzyk, Peter (Journal of Combinatorial Optimization)
We consider online optimization problems in which certain goods have to be acquired in order to provide a service or infrastructure. Classically, decisions for such problems are considered as final: one buys the goods. However, in many real world applications, there is a shift away from the idea of buying goods. Instead, leasing is often a more flexible and lucrative business model. Research has realized this shift and recently initiated the theoretical study of leasing models (Anthony and Gupta in Proceedings of the integer programming and combinatorial optimization: 12th International IPCO Conference, Ithaca, NY, USA, June 25–27, 2007; Meyerson in Proceedings of the 46th Annual IEEE Symposium on Foundations of Computer Science (FOCS 2005), 23–25 Oct 2005, Pittsburgh, PA, USA, 2005; Nagarajan and Williamson in Discret Optim 10(4):361–370, 2013) We extend this line of work and suggest a more systematic study of leasing aspects for a class of online optimization problems. We provide two major technical results. We introduce the leasing variant of online set multicover and give an O(log(mK)logn)-competitive algorithm (with n, m, and K being the number of elements, sets, and leases, respectively). Our results also imply improvements for the non-leasing variant of online set cover. Moreover, we extend results for the leasing variant of online facility location. Nagarajan and Williamson (Discret Optim 10(4):361–370, 2013) gave an O(Klogn)-competitive algorithm for this problem (with n and K being the number of clients and leases, respectively). We remove the dependency on n (and, thereby, on time). In general, this leads to a bound of O(lmaxloglmax) (with the maximal lease length lmax). For many natural problem instances, the bound improves to O(K2).

Towards On-The-Fly Image Processing - Jungmann, Alexander

Towards Automated Service Composition Under Quality Constraints - Mohr, Felix

Towards a Universal Approach for Monotonic Searchability in Self-stabilizing Overlay Networks - Scheideler, Christian; Setzer, Alexander; Strothmann, Thim Frederik (Proceedings of the 30th International Symposium on Distributed Computing (DISC))
For overlay networks, the ability to recover from a variety of problems like membership changes or faults is a key element to preserve their functionality. In recent years, various self-stabilizing overlay networks have been proposed that have the advantage of being able to recover from any illegal state. However, the vast majority of these networks cannot give any guarantees on its functionality while the recovery process is going on. We are especially interested in searchability, i.e., the functionality that search messages for a specific identifier are answered successfully if a node with that identifier exists in the network. We investigate overlay networks that are not only self-stabilizing but that also ensure that monotonic searchability is maintained while the recovery process is going on, as long as there are no corrupted messages in the system. More precisely, once a search message from node u to another node v is successfully delivered, all future search messages from u to v succeed as well. Monotonic searchability was recently introduced in OPODIS 2015, in which the authors provide a solution for a simple line topology.We present the first universal approach to maintain monotonic searchability that is applicable to a wide range of topologies. As the base for our approach, we introduce a set of primitives for manipulating overlay networks that allows us to maintain searchability and show how existing protocols can be transformed to use theses primitives.We complement this result with a generic search protocol that together with the use of our primitives guarantees monotonic searchability.As an additional feature, searching existing nodes with the generic search protocol is as fast as searching a node with any other fixed routing protocol once the topology has stabilized.

The Monotone Circuit Value Problem with Bounded Genus Is in NC - Abu-Khzam, Faisal N.; Li, Shouwei; Markarian, Christine; Meyer auf der Heide, Friedhelm; Podlipyan, Pavel (Proceedings of the 22nd International Conference on Computing and Combinatorics (COCOON))
We present an efficient parallel algorithm for the general Monotone Circuit Value Problem (MCVP) with n gates and an underlying graph of bounded genus k. Our algorithm generalizes a recent result by Limaye et al. who showed that MCVP with toroidal embedding (genus 1) is in NC when the input contains a toroidal embedding of the circuit. In addition to extending this result from genus 1 to any bounded genus k, and unlike the work reported by Limaye et al., we do not require a precomputed embedding to be given. Most importantly, our results imply that given a P-complete problem, it is possible to find an algorithm that makes the problem fall into NC by fixing one or more parameters. Hence, we deduce the interesting analogy: Fixed Parameter Parallelizable (FPP) is with respect to P-complete what Fixed Parameter Tractable (FPT) is with respect to NP-complete. Similar work that uses treewidth as parameter was also presented by Elberfeld et al. in [6].

Systematic evaluation of peer-to-peer systems using PeerfactSim.KOM - Feldotto, Matthias; Graffi, Kalman (Concurrency and Computation: Practice and Experience)
Comparative evaluations of peer-to-peer protocols through simulations are a viable approach to judge the performance and costs of the individual protocols in large-scale networks. In order to support this work, we present the peer-to-peer system simulator PeerfactSim.KOM, which we extended over the last years. PeerfactSim.KOM comes with an extensive layer model to support various facets and protocols of peer-to-peer networking. In this article, we describe PeerfactSim.KOM and show how it can be used for detailed measurements of large-scale peer-to-peer networks. We enhanced PeerfactSim.KOM with a fine-grained analyzer concept, with exhaustive automated measurements and gnuplot generators as well as a coordination control to evaluate sets of experiment setups in parallel. Thus, by configuring all experiments and protocols only once and starting the simulator, all desired measurements are performed, analyzed, evaluated, and combined, resulting in a holistic environment for the comparative evaluation of peer-to-peer systems. An immediate comparison of different configurations and overlays under different aspects is possible directly after the execution without any manual post-processing.

Using Deep Convolutional Neural Networks in Monte Carlo Tree Search - Graf, Tobias; Platzner, Marco (Computer and Games)

Monte-Carlo Simulation Balancing Revisited - Graf, Tobias; Platzner, Marco (IEEE Computational Intelligence and Games)

Verifying Worst-Case Completion Times for Reconfigurable Hardware Modules using Proof-Carrying Hardware - Wiersema, Tobias; Platzner, Marco (Proceedings of the 11th International Symposium on Reconfigurable Communication-centric Systems-on-Chip (ReCoSoC 2016))
Runtime reconfiguration can be used to replace hardware modules in the field and even to continuously improve them during operation. Runtime reconfiguration poses new challenges for validation, since the required properties of newly arriving modules may be difficult to check fast enough to sustain the intended system dynamics. In this paper we present a method for just-in-time verification of the worst-case completion time of a reconfigurable hardware module. We assume so-called run-to-completion modules that exhibit start and done signals indicating the start and end of execution, respectively. We present a formal verification approach that exploits the concept of proof-carrying hardware. The approach tasks the creator of a hardware module with constructing a proof of the worst-case completion time, which can then easily be checked by the user of the module, just prior to reconfiguration. After explaining the verification approach and a corresponding tool flow, we present results from two case studies, a short term synthesis filter and a multihead weigher. The resultsclearly show that cost of verifying the completion time of the module is paid by the creator instead of the user of the module.

An Approach to Non-Destructive Testing of Aged Polymers - Moritzer, Elmar; Hüttner, Matthias; Henning, Bernd; Webersen, Manuel

Molekularen Schäden auf der Spur - Moritzer, Elmar; Hüttner, Matthias; Henning, Bernd; Webersen, Manuel (Kunststoffe)

Detecting Molecular Damage - Moritzer, Elmar; Hüttner, Matthias; Henning, Bernd; Webersen, Manuel (Kunststoffe International)

Non-destructive characterization of hygrothermally aged polymers - Moritzer, Elmar; Hüttner, Matthias; Henning, Bernd; Webersen, Manuel

Ultraschallbasierte Charakterisierung von gealterten Polymeren - Moritzer, Elmar; Hüttner, Matthias; Henning, Bernd; Webersen, Manuel (Jahresmagazin Kunststofftechnik 2016)

Zerstörungsfreie Charakterisierung des hydrothermischen Alterungsverhaltens von Polymeren - Webersen, Manuel; Hüttner, Matthias; Bause, Fabian; Moritzer, Elmar; Henning, Bernd
In der zerstörungsfreien Werkstoffprüfung sind bereits zahlreiche Verfahren etabliert, deren Ziel die Detektion makroskopischer Defekt- und Fehlstellen (z.B. Risse, Poren, Fremdeinschlüsse) ist. Insbesondere bei Polymerwerkstoffen muss jedoch auch die Materialalterung auf molekularer Ebene berücksichtigt werden, die sich (zumeist negativ) auf die Materialkenngrößen auswirkt. Gängige Verfahren zur Bestimmung dieser Kenngrößen arbeiten jedoch üblicherweise zerstörend und sind somit beispielsweise für die vorbeugende Instandhaltung oder die Online-Komponentenüberwachung nur eingeschränkt geeignet. In diesem Beitrag wird ein Verfahren zur zerstörungsfreien Charakterisierung des Alterungszustandes von Polymeren vorgestellt. Dazu wird der Zusammenhang zwischen akustisch (zerstörungsfrei, mittels Ultraschall-Transmissionsmessung) bestimmten Kenngrößen und klassisch (zerstörend, z.B. mittels Zugprüfung) bestimmten hydrothermischer Alterung auf das Material Polyamid 6 (PA6) untersucht. Die Ergebnisse Kenngrößen betrachtet. Exemplarisch werden die Auswirkungen zeigen einen engen Zusammenhang zwischen der zerstörend bestimmten Viskositätszahl, die ein Maß für die mittlere Molekülkettenlänge darstellt, und der akustischen Longitudinalwellengeschwindigkeit. Das Molekülkettenabbau (Depolymerisation) bestimmt ist, kann somit auch akustisch und zerstörungsfrei charakterisiert werden. Auf dieser Basis können neuartige, zerstörungsfrei arbeitende Messsysteme entwickelt werden.

Verifikation von Service Kompositionen mit Spin - Dewender, Markus
.

Verifikation von Service Kompositionen mit Prolog - Heinisch, Philipp
.

Insider-resistent Distributed Storage Systems - Eikel, Martina

Preference Learning - Fürnkranz, J.; Hüllermeier, Eyke (Encyclopedia of Machine Learning and Data Mining)

Proceedings 26. Workshop Computational Intelligence KIT Scientific Publishing, Karlsruhe, Germany

Extreme F-measure maximization using sparse probability estimates - Jasinska, K.; Dembczynski, K.; Busa-Fekete, Robert; Klerx, Timo; Hüllermeier, Eyke (Proceedings ICML-2016, 33th International Conference on Machine Learning, New York, USA)

Learning to aggregate using uninorms, in Proceedings ECML/PKDD-2016 - Melnikov, Vitaly; Hüllermeier, Eyke (European Conference on Machine Learning and Knowledge Discovery in Databases, Part II, Riva del Garda, Italy)

Consistency of probalistic classifier trees - Dembczynski, K.; Kotlowski, W.; Waegeman, W.; Busa-Fekete, Robert; Hüllermeier, Eyke (In Proceedings ECML/PKDD European Conference on Maschine Learning and Knowledge Discovery in Databases, Part II, Riva del Garda, Italy)

Predicting the electricity consumption of buildings: An improved CBR approach - Shabani, Aulon; Paul, Adil; Platon, R.; Hüllermeier, Eyke (In Proceedings ICCBR, 24th International Conference on Case-Based Reasoning, Atlanta, GA, USA)

Evaluating tests in medical diagnosis-Combining machine learning with game-theoretical concepts - Pfannschmidt, Karlson; Hüllermeier, Eyke; Held, S.; Neiger, R. (In Proceedings IPMU 16th International Conference on Information Processing and Management of Uncertainty in Knowledge-Based Systems, Part 1, Eindhoven, The Netherlands)

On the Identifiability of models in multi-criteria preference learning - Labreuche, C.; Hüllermeier, Eyke; Vojtas, P.; Fallah Tehrani, A. (Proceedings DA2PL ´2016, Euro Mini Conference from Multiple Criteria Decision Aid to Preference Learning)

Preference-Based Reinforcement Learning Using Dyad Ranking - Schäfer, Dirk; Hüllermeier, Eyke (Proceedings DA2PL ´2016, Euro Mini Conference from Multiple Criteria Decision Aid to Preference Learning)